2013
DOI: 10.1038/bjc.2012.601
|View full text |Cite
|
Sign up to set email alerts
|

Biology of primary breast cancer in older women treated by surgery: with correlation with long-term clinical outcome and comparison with their younger counterparts

Abstract: Background:As age advances breast cancer appears to change its biological characteristics, however, very limited data are available to define the precise differences between older and younger patients.Methods:Over 36 years (1973–2009), 1758 older (⩾70 years) women with early operable primary breast cancer were managed in a dedicated clinic. In all, 813 underwent primary surgery and 575 good quality tumour samples were available for biological analysis. The pattern of biomarkers was analysed using indirect immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 48 publications
8
65
1
1
Order By: Relevance
“…Both authors published similar results using the intrinsic classification. Also within the biological subgroup further differences between the age groups have been described by several other authors [15,16]. These results should be considered for future treatment recommendations.…”
Section: Distribution Of Biological Subtypessupporting
confidence: 62%
“…Both authors published similar results using the intrinsic classification. Also within the biological subgroup further differences between the age groups have been described by several other authors [15,16]. These results should be considered for future treatment recommendations.…”
Section: Distribution Of Biological Subtypessupporting
confidence: 62%
“…Previous reports have demonstrated that aging is associated with less aggressive tumor features and higher rates of hormonal responses (Downey et al, 2007;Passage and McCarthy, 2007;Thomas and Leonard, 2009;Syed et al, 2013;Thapa et al, 2013;Wei et al, 2014). In the present study, most (74%) elderly BC patients were hormone receptor-positive.…”
Section: Discussionsupporting
confidence: 58%
“…However, in older frail patients, or those with a number of comorbidities and limited life expectancy and also those with a number of social issues, surgery may not be the appropriate Reproduced from [9]. Management of operable primary breast cancer in older women Review answer.…”
Section: Surgery Versus Nonoperative Therapymentioning
confidence: 99%
“…Definitions of the older population in these studies also vary, for example, using postmenopausal status or age at diagnosis as cut-offs (55, 60, 65 and 70 years). The authors' group has also attempted to compare the biology of breast cancers in younger versus older women managed in one single institution and using the same laboratory methodology [9]. Not only was a changing pattern with age shown but also a new cluster with distinct biological pattern ('low ER luminal') has been identified in the older cohort (Figures 1 & 2).…”
mentioning
confidence: 99%